Urban wetland landscape patterns and cooling effects in Guilin utilizing GF-1/6 and SDGSAT-1 data - Zibo Meng; Guozhuang Shen; Jingjuan Liao; Yujuan Guo; Jiepeng Li (International Journal of Digital Earth)
Urban wetlands are vital components of urban ecosystems. As urbanization and climate change continue to increase, understanding the distribution and ecological benefits of urban wetlands is crucial for effective wetlands conservation and urban planning. This study used GF-1/6 Panchromatic and Multispectral Scanner imagery and a two-stage classification approach combining object-oriented random forest and knowledge-based hierarchical decision trees to generate a 2 m resolution urban wetland dataset for Guilin in 2023. The research further analyzed the impact of human activities on wetland landscapes using SDGSAT-1 Glimmer Imager data and assessed the cooling effect of wetlands by retrieving land surface temperatures from SDGSAT-1 Thermal Infrared Spectrometer data. The findings indicated that higher human activity levels led to increased wetland fragmentation and complexity. Areas with more human activities exhibited greater wetland diversity and more uniformly distributed wetland patches. Urban wetlands were found to significantly lower temperatures, with the cooling effect being more pronounced in the growing season, especially in smaller wetlands located in densely built-up urban areas. These results highlight the importance of wetland conservation in mitigating the urban heat island effect and provide valuable insights for wetland management in rapidly urbanizing cities like Guilin.